Epidemiology of Schistosoma and Gastrointestinal Parasites in Goats: A Slaughterhouse-Based Study from Malwa Region, Madhya Pradesh, India - Solanki, Himanshi; Agrawal, Vivek; Shakya, Mukesh; Kumar Jaiswal, Amit; S Choudhary, Nidhi; Jain, Rupesh (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Gastrointestinal (GI) parasitic infections, including those caused by Schistosoma species, represent a major constraint to goat health and  productivity. This research aimed to elucidate the prevalence and epidemiological dynamics of Schistosoma and other GI parasites in  goats slaughtered in the Malwa region of Madhya Pradesh, India. A total of 312 fecal and mesenteric tissue samples were systematically  collected from goats at the Mhow Cantonment Slaughterhouse during the summer and monsoon seasons of 2024. Diagnostic  assessments were performed using flotation, sedimentation, and McMaster techniques, supplemented by morphological identification  of Schistosoma worms and eggs. The findings revealed a significantly higher prevalence of GI parasites during the monsoon season  (p
Keywords: Epidemiological dynamics; Gastrointestinal parasites; Goat; Parasitic burden; Schistosoma spp